The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fneur.2019.01341
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Vestibular Function and Imaging of the Semicircular Canals in DFNA9 Patients

Abstract: Background and Purpose: Radiologic abnormalities on computed tomography (CT), including narrowing or sclerosis of the semicircular canals (SCCs), and T2-weighted magnetic resonance imaging (MRI), including signal loss in the SCC, have been reported as potential biomarkers in patients with P51S mutations in the COCH gene (i.e., DFNA9). The aim of our study was to correlate caloric responses through electronystagmography (ENG) data with imaging results in DFNA9 patients. Materials and Methods: A retrospective st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 19 publications
2
12
2
Order By: Relevance
“…Ihtijarevic et al (26) demonstrated a correlation between hypofunction of caloric responses in patients with focal sclerosis on CT and T2-weighted MRI signal loss, but this was not confirmed with the present study. However, a correlation was observed between vHIT VOR gains in all SCC separately and the presence of MRI lesions.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Ihtijarevic et al (26) demonstrated a correlation between hypofunction of caloric responses in patients with focal sclerosis on CT and T2-weighted MRI signal loss, but this was not confirmed with the present study. However, a correlation was observed between vHIT VOR gains in all SCC separately and the presence of MRI lesions.…”
Section: Discussioncontrasting
confidence: 99%
“…However, similar lesions were also observed in another cohort consisting of CI candidates who were not carrying the p.P51S COCH -mutation. These radiologic lesions were only observed in case patients had reached similar stages of (advanced) hearing and vestibular deterioration as carriers, and they were far less prevalent compared to DFNA9 patients (26).…”
Section: Discussionmentioning
confidence: 94%
“…Previous research has demonstrated that mutations in the COCH gene cause DFNA9, an autosomal dominant disorder that causes progressive sensorineural hearing loss associated with vestibular dysfunction (50,(52)(53)(54)(55). Mutations can cause misfolding and progressive accumulation of mutant proteins leading to degeneration of dendrites and loss of vestibular and cochlear neurons.…”
Section: Cochlinmentioning
confidence: 99%
“…Progressive vestibular dysfunction starts at a similar age and evolves toward bilateral vestibular function loss (bilateral vestibulopathy, BVP). BVP causes oscillopsia and imbalance while walking (especially in the dark) (75)(76)(77)(78)(79)(80)(81)(82)(83). Currently, no treatment is available to prevent or slow down sensorineural hearing loss or BVP in DFNA9 patients.…”
Section: Challenges and Opportunities For Disease-modifying Therapiesmentioning
confidence: 99%